an = an-1 + 3
where a1 has to be known, I conclude that a1 = 2
I don't understand why n>2, I was expecting n>1
Ok, lets assume our terms are 2, 5, 8 ..... , each term is 3 more than the previous one
You could just grind it out and find the 12th terms , there are not too many for that.
However, I can translate this one to
an = 3n - 1 , that will produce our sequence 2, 5, ...
so a12 = 3(12) - 1 = 35
how do you find the 12th term of the sequence an= an-1+3 ( the n and n-1 are subscript) n>2 (also equal to)? I understand how to find the first six terms,but how do you use that to find the 12th . Thanks
2 answers
斗鱼版权保护投诉指引 - 斗鱼